Promoting community resilience through disaster education: Review of community-based interventions with a focus on teacher resilience and well-being - Fu, Qingchen; Zhang, Xing (PloS one, 2024)
Teachers play a pivotal role, both as educators and community leaders at the heart of any communities. This study seeks to address: "How do community-based interventions influence teacher resilience and well-being in the context of disaster education, and consequently, how does this affect overall community resilience?" Employing the rigorous PRISMA systematic review approach, we examined relevant studies, emphasizing the relationship between teacher resilience, well-being, and the efficacy of community-based disaster education interventions. 47 studies met the specific inclusion criteria and were included in in-depth analysis. This study identified a set of key interventions that have demonstrably boosted teacher resilience and well-being. There was a discernible positive relationship between teacher resilience and the effectiveness of community disaster education initiatives. The relationship between teacher resilience, their well-being, and effective community-based disaster education interventions is intricate and multifaceted. Enhanced teacher resilience contributes substantially to the success of disaster education programs. The interplay between teacher and community resilience emerged as a complex, symbiotic relationship, with teacher well-being acting as a cornerstone for effective community-based interventions. Reinforcing teacher resilience and well-being is integral to the success of community-based disaster education initiatives. Ensuring their well-being not only enhances educational outcomes but also fortifies community resilience. Teachers play a pivotal role in not only educating the younger generation but also in enhancing community resilience. Thus, any strategy aimed at supporting community resilience must integrate comprehensive measures to ensure the well-being and resilience of teachers. This nexus between education and community resilience emphasizes the necessity for integrated, holistic, and community-centric approaches to disaster management.